In-house three-dimensional printing for surgical planning: learning curve from a case series of temporomandibular joint and related disorders - Godinho, Miguel R.; Mestrinho, Lisa A. (Frontiers in Veterinary Science, 2024)
3D printed models can improve the understanding of the structural anatomic changes in cases of temporomandibular joint ankylosis and pseudoankylosis leading to closed jaw locking. Their use in pre-surgical planning and intraoperative guidance has been reported, contributing to the predictability and success of these surgery procedures, which can be quite complex, especially in small animal patients. The use and production of 3D tools and models remain challenging and are so far limited to institutions with high (economical and human) resources. This study aims to propose simplified workflows using open-source software to facilitate an in-house 3D printing process. To illustrate this, three cases of temporomandibular joint ankylosis and one of pseudoankylosis were reviewed, where in-house 3D printed models were used for client communication and surgical management. The 3D models were segmented from computed tomography and printed via stereolithography. They were used to support discussion with clients (n = 4), to allow surgeons to pre-surgical plan and practice (n = 4) and for intraoperative guidance during surgery (n = 2). Surgical cutting guides were produced in one case to improve precision and define more accurately osteotomy lines. It is essential to consider the initial time and financial investment required for establishing an in-house 3D printing production, particularly when there is a need to produce biocompatible tools, such as surgical cutting guides. However, efficient and streamlined workflows encourage the integration of this technology, by accelerating the printing process and reducing the steep learning curves, while open-source software enhances accessibility to these resources.